Induction chemotherapy with paclitaxel, carboplatin and cetuximab for locoregionally advanced nasopharyngeal carcinoma: A single-center, retrospective study - Takeshita, Naohiro; Enokida, Tomohiro; Okano, Susumu; Fujisawa, Takao; Wada, Akihisa; Sato, Masanobu; Tanaka, Hideki; Tanaka, Nobukazu; Motegi, Atsushi; Zenda, Sadamoto; Akimoto, Tetsuo; Tahara, Makoto (Frontiers in Oncology, 2022)
Background: The addition of induction chemotherapy (IC) before chemoradiotherapy (CRT) has improved survival over CRT alone in locoregionally advanced nasopharyngeal cancer (LA-NPC). Nevertheless, this population would benefit from further development of a novel IC regimen with satisfactory efficacy and a more favorable safety profile. Methods: We retrospectively assessed 29 LA-NPC patients who received the combination of paclitaxel (PTX), carboplatin (CBDCA), and cetuximab (Cmab) (PCE) as IC (IC-PCE) at the National Cancer Center Hospital East between March 2017 and April 2021. IC-PCE consisted of CBDCA area under the plasma concentration-time curve (AUC) = 1.5, PTX 80 mg/m2, and Cmab with an initial dose of 400 mg/m2 followed by 250 mg/m2 administered weekly for a maximum of eight weeks. Results: Patient characteristics were as follows: median age, 59 years (range 24–75); 0, 1 performance status (PS), 25, 4 patients; and clinical stage III/IVA/IVB, 6/10/13. The median number of PCE cycles was 8(1-8). After IC-PCE, 26 patients received concurrent cisplatin and radiotherapy (CDDP-RT), one received concurrent carboplatin/5-fluorouracil and radiotherapy (CBDCA/5-FU-RT), and two received RT alone. The % completion of CDDP-RT was 88.5%. The response rate was 75.9% by IC and 100% at completion of CRT. The 3-year recurrence-free survival, locoregional failure-free survival, distant recurrence-free survival, and overall survival were 75.9%, 79.3%, 84.3%, and 96.3%, respectively. The incidence of adverse events of grade 3/4 was 34.5% during IC and 44.8% during CRT. Conclusion: IC-PCE is feasible and effective for LA-NPC and may be a treatment option for this disease.